Maternal newborn : nursing care plans - Green, Carol J. (Burlington, MA : Jones & Bartlett Learning, 2016)
Explains how to assess, plan, provide, and evaluate care for pregnancy, delivery, recovery, abnormal conditions, and newborn care. Features more than 65 of the most common and high-risk care plans for nursing care using the nursing process approach, this text includes NIC interventions, discussions on collaborative problems, key nursing activities, signs and symptoms, and diagnostic studies.
Section I Introduction -- 1. How To Use This Book -- Section II Generic Care Plans -- 2. Nursing Care Plans (Generic) -- 3. Collaborative Care Plans (Generic) -- Section III Antepartum Care -- 4. Normal Pregnancy -- 5. Pregnancy Complicated by Medical and Other Conditions -- 6. Gestational Complications -- Section IV Intrapartum Care -- 7. Normal Intrapartum -- 8. Intrapartum Complications -- Section V Postpartum Care -- 9. Normal Postpartum Care -- 10. Postpartum Complications -- Section VI Care of the Newborn -- 11. Normal Newborn Care -- 12. Neonatal Complications.
Includes bibliographical references and index.
Keywords: Maternal-child nursing -- Methods; Patient care planning; Nursing assessment -- Methods; Pregnancy; Infant, Newborn